Can cooperative video games encourage social and motivational inclusion of at‐risk students?. (30th July 2018) - Hanghøj, Thorkild; Lieberoth, Andreas; Misfeldt, Morten
Abstract: Can the challenges encountered in cooperative video games encourage classroom inclusion? And can this experience be translated into curriculum engagement? This study describes a 3 week intervention with game‐based learning activities in eight lower secondary classrooms ( n  = 190). The intervention combined the use of the co‐op action role‐playing game Torchlight II and analogue gamification aimed at including 32 students challenged by social difficulties and lack of motivation. The video game was used to create more inclusive classrooms by increasing students' opportunities for participation through collaboration in teams. The students also participated in game‐related Danish (L1) and Mathematics activities. Effects on social well‐being, learning and motivational patterns were measured through teacher assessment combined with the Children's Perceived Locus of Causality‐scales. The results show multidimensional effects including positive impact on at‐risk students' well‐being and reduced experiences of external regulation to participate in Mathematics and Danish. The qualitative analysis not only confirms the positive findings, but also shows how the intervention created ambiguities surrounding the relationship between game activities and curriculum‐related assignments. The findings indicate that the impact of game‐based classrooms is not due to their fun element, but rather how they enable reframing of social participation and students' engagement with the curriculum.